La equidad de género en el fútbol - Cajas Oña, Juan Gabriel (2017)
The present project research is focused on the eradication of soccer inequality trying in many ways things that women cannot do it because of the fear of being rejected. Also, the society has touched those kind of rejecting things and making all the process as educative, social as cultural, through this way of researching, we want to leave behind these kind of inferiority complexes in the sport field using an adequate integration methodology and socializing to get a good equality allowing the woman to practice in a normal way everything that she wants in order to develop the passion of sporting in her daily life, including the soccer practicing as an interesting sport and not using it as a routine because of the soccer practicing is immerse in physical education and the discrimination take them to the negative things. Nowadays, our principal goal is that woman will have the same rights and responsibilities with the society going on the training process in the wonderful sport such as soccer in the Physical education classes.